MAKNA TRADISI MALAM BAINAI DALAM PERNIKAHAN ADAT MINANGKABAU DI DESA PADANG LAWEH KECAMATAN SUNGAI TARAB KOTA BATUSANGKAR - Dwi Maharani; Aulia Fitri (Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2022)
Indonesia is a country that has a diversity of ethnic groups that have different customs and cultures. From various cultures, each has its own traditions and customs, one of which is the tradition of the Minangkabau, there is a culture, namely a tradition called Malam Bainai. The night of Bainai is to redden the bride's nails with crushed henna leaves. The Bainai night event is held at Anak Daro's house, which is held on the night of the day before the wedding day. The formulation of the problem in this study is